Student Protests. Three Periods of University Governance - Joan Ramon Rodriguez-Amat; Bob Jeffery (tripleC: Communication, Capitalism & Critique)
Exploring the idea of student protests as an autonomous object of research and discussion, this paper leads to the understanding that the transforming role of the university and its governance defines the possibilities for the political role of students. In this perspective, there is a particular constellation of the different forms of higher education governance that provides students with the right and even the responsibility of protesting as politically engaged citizens of the university and of the state. Approaching the transformation of the models of university governance as a set of archaeologically organised states this paper identifies the sequential roles provided to the students and the meaning of their protests and demonstrations. After visiting some antecedents of more contemporaneous student movements and protests, this paper focuses on the UK to explore three manifestations of university governance that can be roughly differentiated as the enduring democratic period that extends from the late 1960s to the late 1980s, the globalisation period that extends from the early 1990s to the mid-2000s and as the post-millennial turn. These periods, embodying three different styles of governance of higher education, not only demonstrate conformity with the political and economic contexts in which they are embeded, they also correspond to particular socio-technological and communicative ecosystems and determine the specificities of the role of the students and their capacity for political action.